2020
DOI: 10.7717/peerj.8667
|View full text |Cite
|
Sign up to set email alerts
|

Element concentrations in pelagicSargassumalong the Mexican Caribbean coast in 2018-2019

Abstract: The massive influx of pelagic Sargassum spp. (sargasso) into the Mexican Caribbean Sea has caused major deterioration of the coastal environment and has affected the tourism industry as well as livelihoods since 2015. Species of Sargassum have high capacity to absorb metals; thus, leachates of sargasso may contribute to contamination by potentially toxic metals when they drain into the sea and into the groundwater when dumped in inadequate land deposits. Valorization of sargasso would contribute to sustainable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(88 citation statements)
references
References 37 publications
(49 reference statements)
10
57
0
Order By: Relevance
“…The levels detected in this study generally fall within the results reported by Rodríguez-Martínez et al [43], but the levels in this study were considerably higher for iron and lower for manganese in all samples. The levels of both phosphorus and potassium in the 'Mixed Sargassum' were above the maximum levels found by Rodríguez-Martínez et al [43]. The levels of cadmium, chromium, copper, lead and manganese in the current study were similar to those found in S. muticum [86].…”
Section: Minerals and Metalssupporting
confidence: 91%
See 4 more Smart Citations
“…The levels detected in this study generally fall within the results reported by Rodríguez-Martínez et al [43], but the levels in this study were considerably higher for iron and lower for manganese in all samples. The levels of both phosphorus and potassium in the 'Mixed Sargassum' were above the maximum levels found by Rodríguez-Martínez et al [43]. The levels of cadmium, chromium, copper, lead and manganese in the current study were similar to those found in S. muticum [86].…”
Section: Minerals and Metalssupporting
confidence: 91%
“…Some elements showed more than a 5-fold difference between their minimal and maximal concentrations [43]. The levels detected in this study generally fall within the results reported by Rodríguez-Martínez et al [43], but the levels in this study were considerably higher for iron and lower for manganese in all samples. The levels of both phosphorus and potassium in the 'Mixed Sargassum' were above the maximum levels found by Rodríguez-Martínez et al [43].…”
Section: Minerals and Metalssupporting
confidence: 89%
See 3 more Smart Citations